Estudio financiero de los bancos offshore del Ecuador durante los períodos 2005 - 2008 - Camacho Palacios, Delia Angelina (2009)
This work was done on the Financial Analysis of Offshore Banks in Ecuador during the period 2005 – 2008, obtaining information directly from the balance sheets of these entities in the studio, where he has observed that these institutions are working efficiently, capacity and responsibility in each of their periods. To be able to fulfill the objectives have been applied research methods, scientific and analytical, as well as the techniques required of an investigative process which will be mentioned primary and secondary sources. To perform financial analysis methods have been applied vertical and horizontal, where through the charts and tables you can see the percentages that reflect each of their accounts. Being able to identify that for the period 2005, the bank has greater representation in the Asset Account is the Pichincha Miami Agency with a 36,47% stake, to dominate the sub-Investment and loan portfolio, followed by Panama to the Pacific 33,57 %, then continues Guayaquil Trust Bank with 25,22% and finally the Continental Overseas with 4,64% share for the period 2006 has been established that has the largest representation with the Panama Pacific 42.13%, followed by Pichincha Miami Agency with 36,65% share, the Trust Bank in Guayaquil 19,09% and Continental Overseas culminates with 2,3% knowing that this entity is in the process of liquidation, for the period 2007 have lead statistics at the Panama Pacific 45,02%, preceding the Pichincha Agency Miami with 39,80%, Guayaquil continues Trust Bank with 13,29% and the lowest is the representative with Continental Overseas 1,89%; displayed for that period in 2008 reflects the greater representation Pichincha Miami Agency with 48,96% and that this entity has been strictly devoted to the recruitment and placement of resources from abroad, continuing with the Panama Pacific 48,10%, then the Continental Overseas with 1,93% and for completing the Guayaquil Trust Bank with 1,01%. In this sequence we verify that for the period 2005 to the account of liabilities, the entity that handles larger items in their balance sheets is the Pichincha Miami Agency with 37,63%, which is mostly under the sub-Obligaciones the Public with 83,48%, then follows the Continental Overseas with 33,99% share, the Trust Bank Guayaquil with 26,32% and culminates with the Continental Overseas 2,06%; also for the look at the period 2006 Panama Pacific with a rate of 40,03%, while the Miami Agency Pichincha closes with 40,50%, then the Guayaquil Trust Bank with 13,45% and the lowest is the representative with Continental Overseas 1,95% since this entity is no longer made but recovered by putting up its portfolio of previous periods that are already subject to another study, by viewing the 2007 financial statements of the period that we have in this account liabilities of the entity that leads the Figures is the Panama Pacific with 44,31%, following the analysis Pichincha Miami Agency with 40,50%, then follow the Guayaquil Trust Bank with 13,45% and finally with 1,74 Continental Overseas %, referring to the 2008 period reflects the entity that maintains the highest figures Pichincha Miami Agency with 52,32% and its largest item is in the Obligations with the public at a 68,78% and interbank transactions in a 29,33%, then continues with the Panama Pacific 45,98%, continuing with Continental Overseas 1,70%, knowing that the Guayaquil Bank Trust reflects no value as this entity is in the process of nationalization. As for the accounts of Heritage in 2005, displays the bank with the highest values in this regard is the Continental Overseas with 33,08% to its highest in the sub-heading of social capital, followed by Panama Pacific with 28,95% participation continues Pichincha Miami Agency with 23,58% and finish Guayaquil Trust Bank with 14,39% share for this period will be observed in exchange for the year 2006 leading figures from Panama to the Pacific Heritage the highest percentage of 57,75%, the declines Pichincha Miami Agency with 25,90% after the Bank Trust Guayaquil with 12,68% and finally with Continental Overseas 3,67%, referring to the period 2007 verifies that the Pichincha Miami Agency has 55,07% share, followed by the Miami Agency Pichincha with 30,76%, followed by Guayaquil Trust Bank with 11,01% and the lowest is the representative with Continental Overseas 3,16%, while for the period 2008 Panama Pacific appears as the most representation with a percentage of 75,49%, below is the Guayaquil Trust Bank with 14,10%, reflecting the change in Pichincha Miami Agency this study period closes with the 5,61% stake, and finally there is the Continental Overseas with 4,80%. One can envisage that in the accounts of expenditure for the period 2005 the largest item is submitted by the Pichincha Miami Agency with a percentage of 37,81%, is continuing with the Panama Pacific 34,81%, followed by the Trust Bank in Guayaquil 26,90% and finally the Continental Overseas with 0,48% in 2006 to the period of this account we can say that the Panama Pacific is 41,52% which is the highest percentage of participation, in turn we also have with the Panama Pacific 34,81%, followed by Guayaquil Trust Bank with 26,90% and finished with Continental Overseas with a minimum rate of 0,48%. Continuing with the analysis during the 2007 Panama Pacific reflects the leading figures of the 44,30% participation, it is noteworthy that this entity is working with all of its operations as normal and efficient, while the Miami Agency Pichincha closes this period with 42,49%, continuing to Guayaquil Trust Bank 13,05% and with a minimum figure this period closes with the Continental Overseas 0,16%, and finally we have that by the year 2008 the highest percentage Panama has the Pacific with 43,34%, followed by Miami Pichincha Agency with 40,14%, then the Guayaquil Trust Bank with 16,46%, and Continental Overseas with 0,08% stake. Referring to the statement of income of the accounting period 2005, we can verify that the Pichincha Miami Agency has 37,39% stake, then the Panama Pacific with 36,85% while the Bank Trust Guayaquil close this period with 23,40% and Continental Overseas with 2,36% for the period 2006 has been established that has the largest representation with the Panama Pacific 47,90%, followed by the Miami Agency Pichincha with 34,59% while Guayaquil, the Bank maintains the Trust 14,98% and finally closed with 2,53% share the Continental Overseas, for the period 2007, we can say that leading figures with the Panama Pacific 44,85%, followed by Pichincha Miami Agency with 44,62%, then there is the Guayaquil Trust Bank with 10,42% and finally there is the Continental Overseas with the minimum rate of 0,11% and for the period 2008 to visualize a greater percentage this item to the Panama Pacific 43,56%, while the Miami Agency Pichincha closes this period with 40,91%, followed by Guayaquil Trust Bank with 14,48% and 1,05% that corresponds to Continental Overseas This work was done on the Financial Analysis of Offshore Banks in Ecuador during the period 2005 – 2008, obtaining information directly from the balance sheets of these entities in the studio, where he has observed that these institutions are working efficiently, capacity and responsibility in each of their periods. To be able to fulfill the objectives have been applied research methods, scientific and analytical, as well as the techniques required of an investigative process which will be mentioned primary and secondary sources. To perform financial analysis methods have been applied vertical and horizontal, where through the charts and tables you can see the percentages that reflect each of their accounts. Being able to identify that for the period 2005, the bank has greater representation in the Asset Account is the Pichincha Miami Agency with a 36,47% stake, to dominate the sub-Investment and loan portfolio, followed by Panama to the Pacific 33,57 %, then continues Guayaquil Trust Bank with 25,22% and finally the Continental Overseas with 4,64% share for the period 2006 has been established that has the largest representation with the Panama Pacific 42.13%, followed by Pichincha Miami Agency with 36,65% share, the Trust Bank in Guayaquil 19,09% and Continental Overseas culminates with 2,3% knowing that this entity is in the process of liquidation, for the period 2007 have lead statistics at the Panama Pacific 45,02%, preceding the Pichincha Agency Miami with 39,80%, Guayaquil continues Trust Bank with 13,29% and the lowest is the representative with Continental Overseas 1,89%; displayed for that period in 2008 reflects the greater representation Pichincha Miami Agency with 48,96% and that this entity has been strictly devoted to the recruitment and placement of resources from abroad, continuing with the Panama Pacific 48,10%, then the Continental Overseas with 1,93% and for completing the Guayaquil Trust Bank with 1,01%. In this sequence we verify that for the period 2005 to the account of liabilities, the entity that handles larger items in their balance sheets is the Pichincha Miami Agency with 37,63%, which is mostly under the sub-Obligaciones the Public with 83,48%, then follows the Continental Overseas with 33,99% share, the Trust Bank Guayaquil with 26,32% and culminates with the Continental Overseas 2,06%; also for the look at the period 2006 Panama Pacific with a rate of 40,03%, while the Miami Agency Pichincha closes with 40,50%, then the Guayaquil Trust Bank with 13,45% and the lowest is the representative with Continental Overseas 1,95% since this entity is no longer made but recovered by putting up its portfolio of previous periods that are already subject to another study, by viewing the 2007 financial statements of the period that we have in this account liabilities of the entity that leads the Figures is the Panama Pacific with 44,31%, following the analysis Pichincha Miami Agency with 40,50%, then follow the Guayaquil Trust Bank with 13,45% and finally with 1,74 Continental Overseas %, referring to the 2008 period reflects the entity that maintains the highest figures Pichincha Miami Agency with 52,32% and its largest item is in the Obligations with the public at a 68,78% and interbank transactions in a 29,33%, then continues with the Panama Pacific 45,98%, continuing with Continental Overseas 1,70%, knowing that the Guayaquil Bank Trust reflects no value as this entity is in the process of nationalization. As for the accounts of Heritage in 2005, displays the bank with the highest values in this regard is the Continental Overseas with 33,08% to its highest in the sub-heading of social capital, followed by Panama Pacific with 28,95% participation continues Pichincha Miami Agency with 23,58% and finish Guayaquil Trust Bank with 14,39% share for this period will be observed in exchange for the year 2006 leading figures from Panama to the Pacific Heritage the highest percentage of 57,75%, the declines Pichincha Miami Agency with 25,90% after the Bank Trust Guayaquil with 12,68% and finally with Continental Overseas 3,67%, referring to the period 2007 verifies that the Pichincha Miami Agency has 55,07% share, followed by the Miami Agency Pichincha with 30,76%, followed by Guayaquil Trust Bank with 11,01% and the lowest is the representative with Continental Overseas 3,16%, while for the period 2008 Panama Pacific appears as the most representation with a percentage of 75,49%, below is the Guayaquil Trust Bank with 14,10%, reflecting the change in Pichincha Miami Agency this study period closes with the 5,61% stake, and finally there is the Continental Overseas with 4,80%. One can envisage that in the accounts of expenditure for the period 2005 the largest item is submitted by the Pichincha Miami Agency with a percentage of 37,81%, is continuing with the Panama Pacific 34,81%, followed by the Trust Bank in Guayaquil 26,90% and finally the Continental Overseas with 0,48% in 2006 to the period of this account we can say that the Panama Pacific is 41,52% which is the highest percentage of participation, in turn we also have with the Panama Pacific 34,81%, followed by Guayaquil Trust Bank with 26,90% and finished with Continental Overseas with a minimum rate of 0,48%. Continuing with the analysis during the 2007 Panama Pacific reflects the leading figures of the 44,30% participation, it is noteworthy that this entity is working with all of its operations as normal and efficient, while the Miami Agency Pichincha closes this period with 42,49%, continuing to Guayaquil Trust Bank 13,05% and with a minimum figure this period closes with the Continental Overseas 0,16%, and finally we have that by the year 2008 the highest percentage Panama has the Pacific with 43,34%, followed by Miami Pichincha Agency with 40,14%, then the Guayaquil Trust Bank with 16,46%, and Continental Overseas with 0,08% stake. Referring to the statement of income of the accounting period 2005, we can verify that the Pichincha Miami Agency has 37,39% stake, then the Panama Pacific with 36,85% while the Bank Trust Guayaquil close this period with 23,40% and Continental Overseas with 2,36% for the period 2006 has been established that has the largest representation with the Panama Pacific 47,90%, followed by the Miami Agency Pichincha with 34,59% while Guayaquil, the Bank maintains the Trust 14,98% and finally closed with 2,53% share the Continental Overseas, for the period 2007, we can say that leading figures with the Panama Pacific 44,85%, followed by Pichincha Miami Agency with 44,62%, then there is the Guayaquil Trust Bank with 10,42% and finally there is the Continental Overseas with the minimum rate of 0,11% and for the period 2008 to visualize a greater percentage this item to the Panama Pacific 43,56%, while the Miami Agency Pichincha closes this period with 40,91%, followed by Guayaquil Trust Bank with 14,48% and 1,05% that corresponds to Continental Overseas This work was done on the Financial Analysis of Offshore Banks in Ecuador during the period 2005 – 2008, obtaining information directly from the balance sheets of these entities in the studio, where he has observed that these institutions are working efficiently, capacity and responsibility in each of their periods. To be able to fulfill the objectives have been applied research methods, scientific and analytical, as well as the techniques required of an investigative process which will be mentioned primary and secondary sources. To perform financial analysis methods have been applied vertical and horizontal, where through the charts and tables you can see the percentages that reflect each of their accounts. Being able to identify that for the period 2005, the bank has greater representation in the Asset Account is the Pichincha Miami Agency with a 36,47% stake, to dominate the sub-Investment and loan portfolio, followed by Panama to the Pacific 33,57 %, then continues Guayaquil Trust Bank with 25,22% and finally the Continental Overseas with 4,64% share for the period 2006 has been established that has the largest representation with the Panama Pacific 42.13%, followed by Pichincha Miami Agency with 36,65% share, the Trust Bank in Guayaquil 19,09% and Continental Overseas culminates with 2,3% knowing that this entity is in the process of liquidation, for the period 2007 have lead statistics at the Panama Pacific 45,02%, preceding the Pichincha Agency Miami with 39,80%, Guayaquil continues Trust Bank with 13,29% and the lowest is the representative with Continental Overseas 1,89%; displayed for that period in 2008 reflects the greater representation Pichincha Miami Agency with 48,96% and that this entity has been strictly devoted to the recruitment and placement of resources from abroad, continuing with the Panama Pacific 48,10%, then the Continental Overseas with 1,93% and for completing the Guayaquil Trust Bank with 1,01%. In this sequence we verify that for the period 2005 to the account of liabilities, the entity that handles larger items in their balance sheets is the Pichincha Miami Agency with 37,63%, which is mostly under the sub-Obligaciones the Public with 83,48%, then follows the Continental Overseas with 33,99% share, the Trust Bank Guayaquil with 26,32% and culminates with the Continental Overseas 2,06%; also for the look at the period 2006 Panama Pacific with a rate of 40,03%, while the Miami Agency Pichincha closes with 40,50%, then the Guayaquil Trust Bank with 13,45% and the lowest is the representative with Continental Overseas 1,95% since this entity is no longer made but recovered by putting up its portfolio of previous periods that are already subject to another study, by viewing the 2007 financial statements of the period that we have in this account liabilities of the entity that leads the Figures is the Panama Pacific with 44,31%, following the analysis Pichincha Miami Agency with 40,50%, then follow the Guayaquil Trust Bank with 13,45% and finally with 1,74 Continental Overseas %, referring to the 2008 period reflects the entity that maintains the highest figures Pichincha Miami Agency with 52,32% and its largest item is in the Obligations with the public at a 68,78% and interbank transactions in a 29,33%, then continues with the Panama Pacific 45,98%, continuing with Continental Overseas 1,70%, knowing that the Guayaquil Bank Trust reflects no value as this entity is in the process of nationalization. As for the accounts of Heritage in 2005, displays the bank with the highest values in this regard is the Continental Overseas with 33,08% to its highest in the sub-heading of social capital, followed by Panama Pacific with 28,95% participation continues Pichincha Miami Agency with 23,58% and finish Guayaquil Trust Bank with 14,39% share for this period will be observed in exchange for the year 2006 leading figures from Panama to the Pacific Heritage the highest percentage of 57,75%, the declines Pichincha Miami Agency with 25,90% after the Bank Trust Guayaquil with 12,68% and finally with Continental Overseas 3,67%, referring to the period 2007 verifies that the Pichincha Miami Agency has 55,07% share, followed by the Miami Agency Pichincha with 30,76%, followed by Guayaquil Trust Bank with 11,01% and the lowest is the representative with Continental Overseas 3,16%, while for the period 2008 Panama Pacific appears as the most representation with a percentage of 75,49%, below is the Guayaquil Trust Bank with 14,10%, reflecting the change in Pichincha Miami Agency this study period closes with the 5,61% stake, and finally there is the Continental Overseas with 4,80%. One can envisage that in the accounts of expenditure for the period 2005 the largest item is submitted by the Pichincha Miami Agency with a percentage of 37,81%, is continuing with the Panama Pacific 34,81%, followed by the Trust Bank in Guayaquil 26,90% and finally the Continental Overseas with 0,48% in 2006 to the period of this account we can say that the Panama Pacific is 41,52% which is the highest percentage of participation, in turn we also have with the Panama Pacific 34,81%, followed by Guayaquil Trust Bank with 26,90% and finished with Continental Overseas with a minimum rate of 0,48%. Continuing with the analysis during the 2007 Panama Pacific reflects the leading figures of the 44,30% participation, it is noteworthy that this entity is working with all of its operations as normal and efficient, while the Miami Agency Pichincha closes this period with 42,49%, continuing to Guayaquil Trust Bank 13,05% and with a minimum figure this period closes with the Continental Overseas 0,16%, and finally we have that by the year 2008 the highest percentage Panama has the Pacific with 43,34%, followed by Miami Pichincha Agency with 40,14%, then the Guayaquil Trust Bank with 16,46%, and Continental Overseas with 0,08% stake. Referring to the statement of income of the accounting period 2005, we can verify that the Pichincha Miami Agency has 37,39% stake, then the Panama Pacific with 36,85% while the Bank Trust Guayaquil close this period with 23,40% and Continental Overseas with 2,36% for the period 2006 has been established that has the largest representation with the Panama Pacific 47,90%, followed by the Miami Agency Pichincha with 34,59% while Guayaquil, the Bank maintains the Trust 14,98% and finally closed with 2,53% share the Continental Overseas, for the period 2007, we can say that leading figures with the Panama Pacific 44,85%, followed by Pichincha Miami Agency with 44,62%, then there is the Guayaquil Trust Bank with 10,42% and finally there is the Continental Overseas with the minimum rate of 0,11% and for the period 2008 to visualize a greater percentage this item to the Panama Pacific 43,56%, while the Miami Agency Pichincha closes this period with 40,91%, followed by Guayaquil Trust Bank with 14,48% and 1,05% that corresponds to Continental Overseas